Analisis Faktor-faktor yang Berhubungan dengan Keteraturan Pengobatan pada Pasien Gangguan Cemas Unit Pelaksana Teknis Daerah Rumah Sakit Jiwa Prof Dr. V.l. Ratumbuysang Provinsi Sulawesi Utara - Tudus, Gabriella E.; Kaunang, Theresia M.D.; Langi, F.L.Frederik G. (Neolectura, 2024)
Anxiety is an emotion without an object or energy that cannot be observed directly and depends on a person's subjective experience. The study aims to determine what factors are associated with treatment regularity. Research Methods Mix Methods with a Sequential Explanatory approach. Quantitative research samples using total sampling, the number of respondents 192, qualitative samples 10 informants. The results of research using chi square have been obtained on the variable predisposing characteristics (age and gender) p-value = 0.637 and 0.0910 (p>?), education and occupation p-value = 0.076 & 0.161 (p>?), variable enabling characteristics (health insurance) p-value = 0.590 (p>?). logistic regression statistical test results (p>0.05) have no relationship. The results of qualitative research are the three informants have motivation when believing in the effectiveness of treatment naum economic limitations and experiencing obstacles to reach health access. The research conclusion is that there is an influence of motivation, affordability and achievement of access and effective communication on treatment regularity. The suggestion of this research is that hospital institutions can improve quality and facilities and quality in order to provide maximum service.